Study on fatigue characteristics of anti-stripping sandstone asphalt mixture after water immersion - Zhang, Dabin; Zhang, Zhanli; Huang, Tuo; Huang, Zibei; Zhou, Zihang; Huang, Jianhong (Frontiers in Materials, 2025)
The insufficient adhesion between sandstone aggregates and asphalt binders makes the mixture susceptible to fatigue cracking under moisture conditions, limiting the widespread application of sandstone aggregates. Thus, two non-amine anti-stripping agents, XT-1 (XT) and PM-JL-06A (PM), were selected to enhance the adhesion properties of sandstone asphalt mixtures. First, the type and optimal dosage of anti-stripping agents were determined through three indicators and the boiled method test. Then, four point bending strength tests with different loading rates were carried out on the immersion and non-immersion sandstone asphalt mixture, and on this basis, four point bending fatigue test and fatigue residual strength test were carried out. The results show that compared to the XT anti-stripping agent, the PM agent more effectively enhances the adhesion of sandstone–asphalt mixtures, raising the adhesion grade from level 3 to above level 4 at an optimal dosage of 0.4%. Compared with conventional SBS-modified sandstone asphalt mixtures, PM-modified mixtures showed a 5.3% average increase in dynamic load strength under dry conditions and an 8.4% improvement under water immersion conditions. Furthermore, the addition of PM anti-stripping agent increased the fatigue life by 33.8% under dry conditions and 38.9% under water immersion conditions. Notably, PM modification significantly reduced the damage factor and damage sensitivity of the mixture under cyclic loading while substantially decreasing the fatigue strength decay rate.